La-doped TiO2 Nanoparticles for Photocatalysis: Synthesis, Activity in Terms of Degradation of Methylene Blue Dye and Regeneration of Used Nanoparticles - Verma V.; Singh S.V. (My University, 2025)
In this study, bare and Lanthanum (La)-doped TiO2 photocatalysts Ti1−xLa xO2 (x = 0.00–0.025) were prepared by employing a solution-combustion procedure. In this, citric acid was utilized as fuel and as a complexing agent. The prepared photocatalysts were characterized by FTIR, FE-SEM, XRD, DRS and XPS. The XRD confirms that prepared TiO2 photocatalysts have only the anatase phase, and also, crystallite size was calculated which is 30.16 and 19.90 nm for bare and Ti0.985La0.015O2, respectively. The DRS shows that with increasing the doping concentration of La in TiO2, a continuous shifting in absorbance towards the visible light region was observed. The FTIR determines the O–H band, Ti–O–La, and several other functional groups present in the synthesized bare and La-doped TiO2 photocatalysts. The XPS spectra confirm the existence of all expected elements (Ti, O, and La) in the synthesized photocatalysts. The FE-SEM confirms spherical shape of prepared photocatalysts, and particle size of bare and Ti0.985La0.015O2 was 32.28 and 22.24 nm, respectively, which agrees with XRD data. Photocatalytic breakdown of methylene blue (MB) dye in its aqueous solutions of different concentrations (10, 20, 30, 40 and 50 ppm) was found to be first order. The best activity was shown by Ti0.985La0.015O2, and it was better than the commercial aeroxide P-25 photocatalyst. The Ti0.985La0.015O2 catalyst could be regenerated and reused up to five times with a minor loss in degradation efficiency of MB dye (30 ppm) about 7.85% at the end of fifth cycle, however, with fresh catalyst degradation was 88.71%. © 2023, King Fahd University of Petroleum & Minerals.